PENGEMBANGAN MATERI PERENCANAAN KARIR SISWA SMA SEDERAJAT - Rezkisari, Yohana; Umari, Tri; Arlizon, Raja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Everyone needs a job to work. In society there are many differenttypes of work, each individual has the freedom to choose a career or a job as well as aview of life in the future, followed by responsibility, which is responsible for theconsequences arising from the choice. The responsibility of a person not only focus andcentered on himself, but also with other people seimbang.Materi was prepared usingthe methods of research and development (R & D). The purpose of this research is 1)Establishment of Career Planning material that is suitable for students of Senior HighSchool. 2) To determine the quality of material produced Career Planning. Thismaterial is validated by the supervisor I, II lecturers, teachers guidance and counseling,as well as 29 students of Senior High School. This material is tested to the student withthe allocation of time of 4 hours of lessons (4 x 45 '). This material consists of a sense ofCareer Planning, Interest and Talent, Career planning purposes, the forms of highereducation in Indonesia and fields of work, steps Career Planning. The results of thedevelopment of this material indicates the quality of the material produced in thecategory